Location theory - Beckmann, Martin J. (New York : Random House, 1968)
This book provide a systematic exposition of the theory of location at the level of intermediate and advanced undergraduate economics.
Includes bibliographical references.
asm 21/01/19
Loans
Keywords: Industrial location; Industries; Location theory